Symmetry Two-axis Tilt Angle Capacitive Sensor System - Thi Thuy Ha, Tran; Dac Hai, Nguyen; Thanh Tung, Bui (VNU Journal of Science: Mathematics - Physics; Vol 35 No 2DO - 10.25073/2588-1124/vnumap.4334, 2019)
Abstract: This paper presents the design, fabrication and operation of a highly symmetrical two-axis capacitive sensor. The proposed sensor consists of five electrodes, including of an excitation electrode and two pairs of sensing electrodes with exactly the same dimensions, arranged at identified symmetrically locations on a 3D printed hollow sphere, which containing dielectric medium formed by the partly filled oil and the remaining air. The proposed sensor can measure the tilt angle about the x -axis and y -axis with symmetrical outputs. The proposed sensor is fabricated using a rapid prototyping technology and mounted on the surface of a printed circuit board (PCB) for mechanical packaging and signal processing. Experimental measurement results show that the sensor system can measure the tilt angle in both the x- and y -axis with sensitivity of 103 mV/degree and resolution of ±1 degree in the range of -30 degree to +30 degree. This sensor system can be used in many military and consumer applications. Keywords: Capacitive sensor, Fluidic sensor, Two-axis tilt angle sensor. References [1] Y.L. Chen, Application of tilt sensors in human–computer mouse interface for people with disabilities, IEEE Trans. Neural. Syst. Rehabil. Eng. 9 (2001) 289-294. http://doi.org/10.1109/7333.948457. [2] R. Dai, R. B. Stein, B.J. Andrews, K.B. James, M. Wieler, Application of tilt sensors in Functional Electrical Stimulation, IEEE Trans. Rehabil. Eng. 4 (1996) 63-72. http://doi.org/10.1109/86.506403. [3] W.J. Perkins, B.F. Stenning, Control units for operation of computers by severely physical handicapped persons, J. Med. Eng. Technol. 10 (1986), 21-23. https://doi.org/10.3109/03091908609044332. [4] Y.L. Chen, F.T. Tang, W.H. Chang, M.K. Wong, Y.Y. Shih, T.S. Kuo, The new design of an infrared-controlled human–computer interface for the disabled, IEEE Trans. Rehab. Eng. 7(1999) 474-481. http://doi.org/10.1109/86.808951. [5] L. Zhao, E. M. Yeatman, Micro Capacitive Tilt Sensor for Human Body Movement Detection, IFMBE Proceedings 13 (2007) 195-200. https://doi.org/10.1007/978-3-540-70994-7_34. [6] S. Mangan, J. Wang, Q.H. Wu, Measurement of the road gradient using an inclinometer mounted on a moving vehicle, Proceedings of the IEEE International Symposium on Computer Aided Control System Design, Glasgow, UK, (2002) 80-85. https://doi.org/10.1109/CACSD.2002.1036933. [7] M. Schmela, T. Döring, A.P.B Gómez, A. Roesch. Solar Power in Europe: Status and Outlook, in Trevor M. Letcher, Vasilis M. Fthenakis (Eds), A Comprehensive Guide to Solar Energy Systems, Academic Press (2018) 37-52, ISBN 9780128114797, https://doi.org/10.1016/B978-0-12-811479-7.00003-8. [8] C.H. Lee, S.S. Lee, Study of a capacitive tilt sensor with a metallic ball, ETRI Journal 36 (2014) 361-366. https://doi.org/ 10.4218/etrij.14.0113.0671. [9] S. Das, A Simple, Low Cost Optical Tilt Sensor, Int. J. Electron. Electr. Eng. 2 (2014) 235-241. https://doi.org/ 10.12720/ijeee.2.3.235-241. [10] S.M. Kuo, C.H. Lin, Micro-impedance inclinometer with wide-angle measuring capability and no damping effect, Sensors and Actuators A: Physical 143 (2008) 133-119. https://doi.org/10.1016/j.sna.2007.08.021. [11] Y.P. Tang, C.G. Chen, Design of Omni-Directional Tilt Sensor Based on Machine Vision, Journal of Sensor Technology 1 (2011) 108-115. https://doi.org/10.4236/jst.2011.14015. [12] J.A. Westphal, M.A. Carr, W.F. Mille,.Sl, Expendable bubble tiltmeter for geophysical monitoring, Rev. Sci. lnstrum. 54 (1983) 415-418. https://doi.org/10.1063/1.1137408 [13] Y. Zhao, J. Yang, B.J. Peng, S.Y. Yang, Experimental research on a novel fiber-optic cantilever-type inclinometer, Optics & Laser Technology 37 (2005), 555-559. https://doi.org/10.1016/j.optlastec.2004.08.006. [14] D. Benz, T. Botzelmann, H. K¨uck, D. Warkentin, On low cost inclination sensors made from selectively metallized polymer, Sensors and Actuators A: Physical 123–124 (2005) 18-22. https://doi.org/10.1016/j.sna.2005.03.044.